M&W fashion / Ahmad Azizi Abdul Razak ...[et al.] - Abdul Razak, Ahmad Azizi; Nor Ihsan, Ahmad Irfan; Emran, Khairul Norhaiqal Fikriz; Rosli, Fatin Rohaina; Amran, Anis Amalyn (2022)
We as partnership, consists of 5 person which are the General Manager, Administration Manager, Marketing Manager, Operation Manager and Financial Manager established the partnership business named M&W Fashion, which is known as the fashion services. This store provides various types of clothing that follow the trend nowadays. It is also suitable for all ages whether male or women. Also, our store has the other product like bag and shoes for male and females designs. Other than that, we also sell a variety of shoes’ accessories such as socks, shoelace, shoe spray and insole which can bring more profit. In addition, this item will also be used as a gift for the purchase of our products at a certain price. In this way we can help our sales to attract the attention of the public. This business begins by applying for a loan from a bank to support our business development. The purpose of established the M&W Fashion is as an alternative for people who seeking the clothes, bags and even shoes in just at one place. In addition, our store is the first store to sell these items in the area where our store is based. So, many people will be focused on our store to get their clothing items. This is an advantage for this business to grow and success in the future. In that case, M&W Fashion can fulfil the demand in those areas because the mission that our store carry is to give the customers consumers an experience of having clothing items they are satisfied with.